Sources and Forms of Financing of Innovative Activities in Germany - Elmira Mekhdyatovna Khayretdinova; Vera Andreevna Zubenko (Мир новой экономики)
Relevance. The purpose of the article is to reveal and analyze some features of the structure and institutional forms of financing research and development in modern Germany, which belongs to the leading countries in the field of innovation. Modern science has proved that improving the competitiveness of both individual enterprises and countries as a whole is impossible without increasing the innovative component in economic development. In the new economic paradigm, scientific and technological progress, knowledge in general act as the main factors of economic growth. Within the framework of the concept “Strategy in the field of high technologies”, adopted in Germany in 2014, innovation policy is considered as the main component of the country’s economic policy, and its most important tasks are stimulating innovations in companies and in society as a whole. Methods. Based on the analysis of relevant publications of the EU, OECD, reports of German Federal agencies, articles by Russian authors on the organization and financing of R&D in the European Union and Germany, the authors show that the business sector is the main source of financing and the sphere of implementation of innovations. At the same time, not only large companies but also small businesses develop and implement innovations, thereby maintaining a high scientific and technical level of the economy. The article emphasizes the more active role of the state than it is in a number of other developed countries, The German state not only finances fundamental research in public and semi-public centers and universities, but also provides selective support to innovative developments in the private sector, including project financing. The authors stress that providing various kinds of support a special preference is given to innovation’s clusters and research networks, as well as regional development programs. Results. The study concluded that the characteristic feature of financing innovation in the private sector in Germany is the active interaction of large companies with banks on the basis of credit agreements. With regard to small business, its contribution to the country’s innovative development is constrained by the underdeveloped institution of venture capital financing. Prospects. The results of this study may be useful in the implementation of the strategy of innovative development of Russia and the development of measures of state support for innovative companies.